Malawi Diagnostic Review of Consumer Protection and Financial Literacy : Volume 2. Comparison with Good Practices - World Bank (World Bank, Washington, DC, 2017)
According to FinScope surveys in 2008 and 2014, the number of financially included adult Malawians grew from 45 percent to 49 percent, and the proportion of adults using formal banking services expanded from 19 percent to 27 percent. These significant improvements were achieved based on Malawi’s Financial Sector Development Strategy for 2010-2015 that identified consumer protection and financial literacy as priorities in developing a financial sector that supports inclusive and sustainable growth. In 2012 the World Bank conducted a diagnostic review in Malawi that aimed to highlight the progress made, compare Malawi’s legal and institutional frameworks with international benchmarks, and provide a series of concrete recommendations. Although key initial steps have been taken in financial consumer protection, especially at the institutional level, Malawi is still at an early stage of development in this area, based on international good practices. Volume 1 of this report focuses on Key Findings and Recommendations from the review. Volume 2 presents a detailed assessment of each financial segment compared to the good practices. It also includes annexes that analyze and provides recommendations on credit reporting, mobile banking services and private pension funds, and a description of the overall legal and institutional frameworks for financial consumer protection in Malawi.